Constraints Faced by Farmers in Utilizing Rice Related Information through Rice Knowledge Management Portal (RKMP) - Kumar, Sunil; Sangeetha, V.; Singh, Premlata; Burman , R. Roy; Bhowmik, Arpan; Kumar, S Arun (Indian Journal of Extension Education, 2017)
Agriculture is a multifaceted enterprise comprising of millions of small and marginal farmers in India. Majority of Indian  farmers are resource poor and illiterate, having tiny or no access to present-day contemporary technologies. Information,  knowledge and technologies available to millions of rural families determine the success in agriculture and rural  development. Rice Knowledge Management Portal (RKMP) is an initiative of Indian Institute of Rice Research (IIRR),  Hyderabad, to cater to the information need of the stakeholders and provide a one-stop solution to all rice related  information. The present investigation was undertaken with an objective to analyse the constraints faced by farmers in  utilising the information available through RKMP. The results showed that farmer face technological, social and  psychological constraints more severely. Among the technological constraints ; lack of updated information' was stood  first (mean rank=6.388) in utilizing the information. Similarly, electricity problem (mean rank =5.350) and poor  connectivity (mean rank =4.831) were also considered as limiting factors among farmers. In case of social constraints  'lack of access to women farmers' (mean rank =3.731) found to be the most limiting factor for using portal information.  Similarly 'lack of institutional support' (mean rank =3.631) and 'less networking among farmers (mean rank =2.813) were  also affected significantly. In case of psychological factors 'techno-phobia'(mean rank =2.219) was found most severe.  Lack of motivation (mean rank =1.794) was least affecting to information management and delivery. Among economical  constraints, cost of computer/smart phone (mean rank= 1.513) was affecting utilization of information provided by portal.  The finding will be helpful in redesigning and modifications needed for reaching upto the grass root level for  disseminating information and making portal more effective for farmers for timely and relevant information.
Keywords: RKMP; constraints; technological; social; psychological; economical